2021
DOI: 10.1155/2021/5543838
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Aphthous Stomatitis Improved after Eradication Therapy for Helicobacter pylori

Abstract: Helicobacterpylori (H. pylori) is a Gram-negative bacterium that colonizes gastric mucosa and is often transmitted through direct contact with saliva, contaminated food or water, and vomit. The majority of the infected individuals remain asymptomatic for a long period. Infection with H. Pylori often presents with dyspepsia, nausea, frequent belching, bloating, abdominal discomfort, burning abdominal pain, and peptic ulcer. A potential association between H. Pylori and recurrent aphthous stomatitis was previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Recurrent aphthous stomatitis (RAS) is regarded as a recurrent painful ulcerative disease that regularly impacts mucosa in the oral cavity. Gao et al (2021) reported a RAS case with a history of 24 years that was cured after treatment for H. pylori , indicating that eradication of H. pylori might relieve RAS symptoms and is a promising RAS therapy.…”
Section: Other Diseasesmentioning
confidence: 99%
“…Recurrent aphthous stomatitis (RAS) is regarded as a recurrent painful ulcerative disease that regularly impacts mucosa in the oral cavity. Gao et al (2021) reported a RAS case with a history of 24 years that was cured after treatment for H. pylori , indicating that eradication of H. pylori might relieve RAS symptoms and is a promising RAS therapy.…”
Section: Other Diseasesmentioning
confidence: 99%
“…Recurrent aphthous stomatitis (RAS) disorder is a popular common recurrent chronic inflammatory disease characterized by painful ulcerations affecting the oral mucous membrane usually at lingual, buccal, and labial mucosa. [ 1 ]…”
Section: Introductionmentioning
confidence: 99%